Identification of prognostic long non-coding RNA and construction of competing endogenous RNA networks in pediatric sepsis - LIU Tiantian; ZHAO Yilin; NING Jingjing; ZHANG Yucai; WANG Chunxia (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To screen a long non-coding RNA (lncRNA) signature and construct a competing endogenous RNA (ceRNA) network associated with the prognosis of pediatric sepsis based on the Gene Expression Omnibus (GEO) database, and explore their potential application value in the prognosis assessment of children with sepsis.Methods·Microarray data in GSE4607, GSE26440, GSE26378, and GSE9692 in the GEO database were used to compare the differences in lncRNA profiles between the survival and non-survival groups of children with septic shock. Then, multivariate linear regression, LASSO analysis, and receiver operating characteristic (ROC) curves were used to evaluate the capacity of the lncRNA signature for predicting the outcome of pediatric sepsis. The potential targeted microRNAs (miRNAs) and their downstream mRNAs, targeted by the screened lncRNAs, were used to construct a protein-protein interaction (PPI) network and perform pathway enrichment analysis.Results·Transcriptomic data from GSE4607, GSE26440, GSE26378 and GSE9692 revealed 55 differentially expressed lncRNAs associated with prognosis, and miR503 host gene (MIR503HG), TAPT1 antisense RNA 1 (TAPT1-AS1), apoptosis-associated transcript in bladder cancer (AATBC), SBF2 antisense RNA 1 (SBF2-AS1), MGC16275, and small nucleolar RNA host gene 15 (SNHG15) were identified as a 6-lncRNA signature (lncSig6) associated with the prognosis of pediatric septic shock by LASSO regression analysis. The area under the ROC curve (AUC) of lncSig6 was 0.859 (95% CI 0.722‒0.996) and 0.854 (95% CI 0.687‒1.000) in internal and external validation, respectively. As lncRNA act as miRNA sponge, a lncRNA-miRNA-mRNA network based on 3 lncRNAs (MIR503HG, SNHG15, and SBF2-AS1) was constructed and involved in the regulation of signaling pathways, including forkhead box O (FoxO) signaling pathway, phosphatidylinositol 3 kinase-protein kinase B (PI3K-AKT) signaling pathway, cell senescence, insulin signaling pathway, hypoxia-inducible protein-1 (HIF-1) signaling pathway and advanced glycation end products (AGEs) and receptor of AGEs (RAGE) signaling pathway.Conclusion·The lncSig6 can be used as an evaluation method to predict the prognosis of septic shock in children, and the constructed ceRNA molecular networks can provide an experimental basis for the study of signaling pathways.